From degrowth to concrete actions: an exploratory study of the role of bottom-up and top-down initiatives in deep sustainability transitions - Teixeira, Paula Inês Cosme (2019)
Debates around ecological and social limits to economic growth and new ways to deal with resource scarcity without compromising human wellbeing have re-emerged in the last few years, especially with the increasing calls for a degrowth approach. This thesis has the main theme of exploring degrowth theory and practice to tackle the multiple social, economic and environmental crisis modern societies are facing. The main motivation for this research was to contribute for translating degrowth theory into pathways for concrete actions. We started by exploring the roots, principles and meanings of degrowth in academic literature. This led into an exploration about how to articulate bottom-up and top-down initiatives into a coherent framework for transition. Then, a group of degrowth scholars were interviewed, to discuss what might be the role of the state and the role of civil society in a degrowth transition, how to articulate values and structure different policy-making processes for being more inclusive and collaborative, and to a certain point how this transformation process can make democracies stronger. The following step was to explore some of the existent theories about sustainability transitions, to better explain a degrowth transition path in theory and to prepare the planning of strategic actions. From these theories, the multi-level perspective was chosen as a conceptual basis. As degrowth requires deep changes in the fundamental structures of current society, this theory was adapted to this particular vision. The next step was to find a method for translating the contribution of the niche innovations (bottom-up initiatives) and the regime reforms (top-down initiatives) to the regime shift in a degrowth direction. At this stage, the degrowth assessment tools were developed, based on the degrowth goals and proposals retrieved from the literature review. To test the developed framework, the assessment tools were applied to the Portuguese context, encompassing two case studies: Sustainability initiatives voluntarily created by civil society and the Green Tax Reform process. The main findings of this work were that: (i) degrowth is not a homogenous vision for a sustainable the future, but a recognition of the plurality of values and legitimate viewpoints that share the overall or parts of the degrowth vision and goals; (ii) degrowth focus is on reducing the scale of human activities and increasing social justice, being efficiency treated marginally; the analysis to a group of Portuguese bottom-up initiatives showed that they are contributing to degrowth goals and are experimenting alternative ways to produce goods and services and to exchange them, even if they do not refer to themselves as degrowth initiatives; (iv) the analysis of the Portuguese green tax reform process showed that there is potential to provoke small changes in parts of the system that can induce behaviour change towards degrowth goals. The main contributions of this work were done at theoretical level, by connecting degrowth vision with democracy and transition studies literature; and at empirical level, with the development of the degrowth assessment tools, which can be used by both practitioners and policy-makers to analyse their contribution to a degrowth transition.